An atypical presentation of autoimmune hepatitis with delayed menarche in a Nigerian adolescent: a case report - Promise Udoka Asogwa; Bruno Basil; Winifred Njideka Adiri; Nelson Ugwu; Gideon Ekene Anigbo; Evaristus Offia; Casmir Orjioke (Journal of Medical Case Reports)
Abstract Background Autoimmune hepatitis is a chronic liver disease marked by immune-mediated inflammation, necrosis, and the potential to progress to cirrhosis if not treated. This case report presents a rare and atypical presentation of autoimmune hepatitis in a Nigerian adolescent girl, highlighting diagnostic challenges in resource-limited settings. The case is unique owing to the absence of jaundice, a common symptom of liver dysfunction, and features such as delayed menarche and bilateral leg swelling. Case presentation The patient was a 16-year-old Black female patient of Igbo ethnicity from Nigeria, who presented with a 6-month history of bilateral leg swelling and delayed menarche. She had no history of jaundice and abdominal pain, and she had no significant past medical history. She was initially misdiagnosed, delaying appropriate management. Following a comprehensive diagnostic workup, including liver function tests, imaging, and autoantibody testing, which were positive for antinuclear and antismooth muscle antibodies, she was correctly diagnosed with type 1 autoimmune hepatitis. Treatment was initiated with corticosteroids (prednisolone) and azathioprine, which resulted in clinical improvement. However, her serum albumin levels remained low as a result of the preexisting cirrhosis. Conclusions This case highlights the diagnostic challenges of autoimmune hepatitis in adolescents, particularly in regions where infectious liver diseases are more commonly suspected. It emphasizes the need for increased awareness and better diagnostic resources to improve early detection and management of autoimmune hepatitis in sub-Saharan Africa. Early intervention with immunosuppressive therapy is essential, even in the absence of classic liver-related symptoms, to prevent progression to advanced liver disease.